Design of Integrated Science Electronic Book Temperature and Heat Material Loaded with Ethnoscience Batik Besurek Bengkulu - Dini Fajar Triana; Sutarno Sutarno; Bhakti Karyadi; Lina Mahardiani; Afrizal Mayub (Universitas Lambung Mangkurat, 2025)
Science learning in schools tends to be theoretical and less related to real contexts, so students have difficulty understanding the application of concepts in everyday life. One of the causes is the lack of teaching materials that integrate local wisdom. This study aims to examine the concepts of science in the local wisdom of making Batik Besurek to be developed as ethnoscience content in integrated science e-books and to determine the level of validity and student response to the product. The method used is research and development (R&D), according to Borg and Gall (1983), using the Model of Educational Reconstruction (MER) approach. Data were obtained through questionnaires, observations, and interviews. The results of the study showed that the process of making Batik Besurek contains the concepts of temperature and heat, expansion, changes in the state of matter, physical changes, heat transfer, and Black's principle, which can be integrated into the content of the Integrated Science Electronic Book. The developed electronic book obtained a very high level of validity with an average V index of 0.86 and a percent agreement of 89.27%. The students' response to the book was also excellent, with an average percentage of 89.42%. The results concluded that the Integrated Science electronic book containing the ethnoscience of Batik Besurek Bengkulu was considered valid teaching material worthy of being tested for effectiveness in future research.